LED Traffic Light with Single Display - Farah Syazana, Roslan; Suliana, Ab Ghani; Muhammad Ikram, Mohd Rashid; Noor Lina, Ramli (2013)
A single display traffic light system is a multifunction system that used bicolor bipolar Light Emitting Diode (LED) to enhance the conventional traffic lights on the road. This traffic light is able to display green, yellow and red color on the same screen by applying the difference current for each color. Besides, the screen also can display turning arrows (right turns and left turns) at the same time. The system design is controlled by Peripheral Interface Microcontroller (PIC) and is simulated by using Proteus software.